PTTL characteristics of glass samples from mobile phones. (March 2020) - Discher, Michael; Woda, Clemens; Lee, Jungil; Kim, Hyoungtaek; Chung, Kisoo; Lang, Andreas
Abstract: Phototransferred thermoluminescence (PTTL) of mobile phone display glass (category A) is systematically investigated to develop a robust measurement protocol for its emergency dosimeter usage after an incident with ionizing radiation. First, optimal readout parameters were defined by varying preheat temperature and holding time preceding violet exposure (405 nm). Next, the detection window of the PTTL measurement was adjusted to optimize the ratio between radiation-induced (RIS) and non-radiation-induced signals (nRIS) of the PTTL. Finally, the developed protocol determines PTTL after preheating to 400 °C and holding for 10 s was tested using the detection window centered at 340 nm. Dosimetric properties such as the PTTL reproducibility and dose response were investigated. PTTL signal stability tests showed that the violet PTTL signal originates from deeper and consequently more thermally stable traps. A signal loss of less than 10% after 10.6 days (254 h) storage was observed. Additionally, TL and PTTL spectra were recorded to investigate the luminescence emissions after beta and gamma irradiation and different UV exposures. PTTL emissions are similar to TL emission. Varying UV energy a qualitative comparison demonstrate that the RIS and nRIS PTTL signal intensities increase significantly with decreasing UV stimulation wavelength. In general, the developed PTTL protocol indicates better signal stability and thus some advantages over other techniques, however, further research is needed to test the potential of a new method for physical retrospective dosimetry. Highlights: PTTL on the display glass extracted from mobile phones is systematically tested. Optimization of the readout parameters and investigation of dosimetric properties. The PTTL method for an additional independent measure as a tool for retrospective dosimetry.